Evaluation of Pulmonary Function after Off- Pump Coronary Artery Bypass Graft Surgery with Thoracic Epidural Analgesia. - Mandal, Naresh Chandra; Sabur, SAMA; Ahsan, NAK; Karmakar, KK (Cardiovascular Journal, 2013)
Background: A substantial reduction of lung volumes and pulmonary function follows cardiac surgery. Pain may prevent effective breathing and coughing, as thoracic epidural analgesia may reduce post operative pain and improve early post operative pulmonary function. We tested the effect of thoracic epidural analgesia (TEA) on pulmonary function after off- pump coronary artery bypass (OPCAB) graft surgery. Methods: 60 patients undergoing off- pump coronary artery bypass (OPCAB) graft surgery were nonrandomized in to two groups. Group-I (30 patients) receiving thoracic epidural analgesia along with general anaesthesia (G/A) but Group-II (30 patients) receiving general anaesthesia alone. Total ventilation time, intensive care unit (ICU) stay, spirometric data, arterial blood gas (ABG) and X-ray chest (CXR) were recorded in postoperative follow-up period. Results: Thirty patients were enrolled in each group. The demographics of the groups were similar. Patients in the epidural group had significantly less pain on the operative day and for the next 2 days. Total ventilation time in hours in Group-I was 6.4±1.0 and in group-II was 10.1±1.8 hours respectively. FVC and FEV1 were significantly different in group-I than group-II. On the postoperative period, ABG was done pre and postoperative period in both groups of patients. Significant differences was found in pao2 and paco2, half an hour after extubation, 1st postoperative day, 2nd postoperative day (p<0.05). Postoperative CXR revealed significant pulmonary complication in group-II than group-I, higher in the epidural group on the first and second postoperative days. There were no complications related to epidural hematoma and no permanent neurologic squeal. Conclusion: Thoracic epidural analgesia yields a slight, but significant improvement in pulmonary function most likely due to a more profound postoperative analgesia. Cardiovascular Journal Volume 6, No. 1, 2013, Page 31-36 DOI: http://dx.doi.org/10.3329/cardio.v6i1.16112